Existimos - Caines, Khadine. (Tufts Archival Research Center, 2019)
Background: The marginalization of people of color is what drives me to have a voice. My body of work looks at the parallel between women of color and endangered plants that are native to the same regions. For example, Malaysian Rafflesia is a piece that was able to create a relationship between a woman native to Malaysia and a Rafflesia, an endangered plant native to southeast Asia, mainly Malaysia, Thailand, Indonesia and the Philippines. By initiating this relationship between the two, I bring light to cultures and people who have been pushed to the side simply by what they look like, and endangered flowers that have no voice of their own; both silenced and invaded for many years. By creating this dialogue, I wish to help them be seen in a space that for many years has been absent of their presence.; Keywords: Printmaking, Woodcut, Relief, Women of color, Sudan, Yemen, Dominican Republic, Hawaii, India, Australia, Plants, Botanical Life, Handmade Paper, Kozo, Abaca, People of Color, Borneo Teak, Bayahibe Rose, 'Akoko, Berberis nilghiriensis, Nubian Desert Palm, Echidnopsis bentii, Miami-born Artisit.